2014
DOI: 10.1016/j.dld.2014.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes as liver damage mirror of HCV related adipogenesis deregulation

Abstract: Hepatitis C virus infection leads to a wide spectrum of liver diseases ranging from mild chronic hepatitis to end-stage cirrhosis and hepatocellular carcinoma. An intriguing aspect of the HCV infection is its close connection with lipid metabolism playing an important role in the HCV life cycle and in its pathogenesis. HCV is known to be a hepatotropic virus; however, it can also infect peripheral blood mononuclear cells (PBMCs). The goal of the current investigation is to compare the adipogenesis profile of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our previously published data indicated that HCV infected patients were characterized by a deep deregulation of some genes involved in the control of lipid metabolism. Accordingly, we demonstrated that this feature was restricted to Hepatitis C virus infection, whereas HBV patients had different features [ 19 ]. Among all, the previously analyzed steatogenic genes (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previously published data indicated that HCV infected patients were characterized by a deep deregulation of some genes involved in the control of lipid metabolism. Accordingly, we demonstrated that this feature was restricted to Hepatitis C virus infection, whereas HBV patients had different features [ 19 ]. Among all, the previously analyzed steatogenic genes (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Liver steatosis and oxidative stress play an important role in liver damage during HCV infection; accordingly, several transcriptional regulators of cholesterol and fatty acid metabolism have been shown to be implicated in HCV infection [ 22 23 ]. In a recent work, we investigated the expression profiles of genes associated to HCV-related steatogenesis in liver biopsies and PBMCs of HCV positive patients [ 19 ]. We highlighted the involvement of different Nuclear Receptor in this phenomenon, such as FXR, LXRs, HNF4.…”
Section: Discussionmentioning
confidence: 99%
“…Human PBMCs from HDs were obtained from 17 individuals attending the local blood transfusion unit of Policlinico 'Tor Vergata' in Rome 31 . PBMCs were separated as previously described 59 . Cell lines and PBMCs were cultured at 37°C in a 5% CO 2 humidified atmosphere in the presence or absence of treatment.…”
Section: Cell Line Culturementioning
confidence: 99%
“…Recruitment of inflammatory cells takes place following injury, such as Kupffer cells (KC), leukocytes, lymphocytes, natural killer cells (NK), and so on. Some of these inflammatory cells can produce compounds that modulate HSC behavior.…”
Section: Angiogenesis and Liver Fibrosismentioning
confidence: 99%